Eksperimen Pembelajaran Matematika Dengan Strategi Thinking Aloud Pair Problem Solving Dan Problem Posing Terhadap Hasil Belajar Ditinjau Dari Kemampuan Penalaran Matematis Siswa Kelas Viii Smp N 3 Colomadu - Bunga Hapsari, Nur Fadhilah, Prof. Dr. Budi Murtiyasa M.Kom (2017)
ABSTRACT This research have three purposes. (1) examine the effect of learning strategies Thinking Aloud Pair Problem Solving and Problem Posing on mathematics learning outcomes, (2) examine the effect of mathematics reasoning ability on mathematics learning outcomes, (3) the interaction between learning strategy and mathematics reasoning ability on mathematics learning outcomes. The type of this research is all students of VIII SMP N 3 Colomadu of academic year 2016/2017. Sample of this research consisted of two classes there are class VIII G as experiment class and class VIII F as control class. The sampling technique is cluster random sampling. Method of data collection used test and documentation. Technique of analyzing data used analysis of variance two paths with different cells. Results of the data analysis with a significance level of 5% was obtained: (1) there is a effect of learning strategies Thinking Aloud Pair Problem Solving and Problem Posing on mathematics learning outcomes, (2) there is a effect of mathematics reasoning ability on mathematics learning outcomes, (3) there is no interaction between learning strategy and mathematics reasoning ability on mathematics learning outcomes. Keywords: mathematics reasoning ability, mathematics learning outcomes, Thinking Aloud Pair Problem Solving, Problem Posing.